2018
DOI: 10.1016/j.nicl.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Local and distant relationships between amyloid, tau and neurodegeneration in Alzheimer's Disease

Abstract: The relationships between β-amyloid (Aβ), tau and neurodegeneration within Alzheimer's Disease pathogenesis are not fully understood. To explore these associations in vivo, we evaluated 30 Aβ PET-positive patients (mean ± sd age 62.4 ± 8.3) with mild probable AD and 12 Aβ PET-negative healthy controls (HC) (mean ± sd age 77.3 ± 6.9) as comparison. All participants underwent 3 T MRI, 11C-PiB (Aβ) PET and 18F-AV1451 (tau) PET. Multimodal correlation analyses were run at both voxel- and region-of-interest levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 83 publications
11
129
1
Order By: Relevance
“…within a lobe, as another study observed in a cohort of AD patients (Iaccarino et al, 2018). Specifically, we found strong correlations between tau deposition and both hypometabolism and atrophy in the occipital lobes, as well as between tau deposition and hypometabolism in the frontal lobes across the atypical AD cohort.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…within a lobe, as another study observed in a cohort of AD patients (Iaccarino et al, 2018). Specifically, we found strong correlations between tau deposition and both hypometabolism and atrophy in the occipital lobes, as well as between tau deposition and hypometabolism in the frontal lobes across the atypical AD cohort.…”
Section: Discussionmentioning
confidence: 56%
“…This knowledge is essential to understand the causes of neurodegeneration and inform new treatments tailored to address the pathophysiology of the disease. Studies have suggested that the regional pattern of Aβ deposition is consistent across clinical phenotypes of AD and is not related to neurodegeneration (Bischof et al, 2016; Iaccarino et al, 2018; La Joie et al, 2012; Ossenkoppele et al, 2015; Ossenkoppele et al, 2016; Rabinovici et al, 2008), while tau topographically matches grey matter atrophy and glucose hypometabolism and can therefore be interpreted as the likely driving force behind neurodegeneration (Dronse et al, 2017; Ossenkoppele et al, 2016; Jennifer L Whitwell et al, 2018; Xia et al, 2017). Additionally, it has been observed that AD pathological proteins may spread along functional brain networks, with strongly connected regions displaying a higher tau burden (Cope et al, 2018; Hoenig et al, 2018; Jones et al, 2017) and amyloid being a partial mediator between functional network failure and tau deposition (Jones et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower hippocampal volume has also been associated with greater tau radiotracer retention in the hippocampus [8,10]. Longitudinal studies including individuals ranging from CN to demented have further found that higher baseline tau tracer retention is associated with greater rates of brain volume loss [11,12] and global cognitive decline [13–15].…”
Section: Introductionmentioning
confidence: 99%
“…While the association between increased oxidative stress and increasing bioenergetic dysfunction, as evidenced by increasing glucose hypometabolism, increased lactate and pyruvate and the development of increasing synaptic dysfunction seen in preclinical AD and APOE ε4 carriers, is not associated with Aβ accumulation [257] (reviewed by [258]), recent research suggests that this might not be the case for tau deposition although findings are mixed [259][260][261]. For example, Bischof and others and Kang et al reported a positive correlation between tau deposition and glucose hypometabolism in cross-sectional studies [259,261].…”
Section: Oxidative Stress and The Development Of Synaptic Dysfunctionmentioning
confidence: 99%